Leucistic Bewick’s Swans - Evans, Mary E; Lebret, Tom (Wildfowl, 1973)
Support for the proposition that the mysterious swan, Cygnus davidi, as being a leucistic variety of Bewick’s Swan Cygnus columbianus bewickii.